Evidence for the involvement of peripheral β-adrenoceptors in delayed liquid gastric emptying induced by dipyrone, 4-aminoantipyrine, and antipyrine in rats - Vinagre, A.M. (Associação Brasileira de Divulgação Científica, 2013)
Dipyrone (Dp), 4-aminoantipyrine (AA), and antipyrine (At) delay liquid gastric emptying (GE) in rats. We evaluated adrenergic participation in this phenomenon in a study in male Wistar rats (250-300 g) pretreated subcutaneously with guanethidine (GUA), 100 mg·kg(−1)·day(−1), or vehicle (V) for 2 days before experimental treatments. Other groups of animals were pretreated intravenously (iv) 15 min before treatment with V, prazosin (PRA; 1 mg/kg), yohimbine (YOH; 3 mg/kg), or propranolol (PRO; 4 mg/kg), or with intracerebroventricular (icv) administration of 25 µg PRO or V. The groups were treated iv with saline or with 240 µmol/kg Dp, AA, or At. GE was determined 10 min later by measuring the percentage of gastric retention (%GR) of saline labeled with phenol red 10 min after gavage. %GR (mean±SE, n=8) indicated that GUA abolished the effect of Dp (GUA vs V=31.7±1.6 vs 47.1±2.3%) and of At (33.2±2.3 vs 54.7±3.6%) on GE and significantly reduced the effect of AA (48.1±3.2 vs 67.2±3.1%). PRA and YOH did not modify the effect of the drugs. %GR (mean±SE, n=8) indicated that iv, but not icv, PRO abolished the effect of Dp (PRO vs V=29.1±1.7 vs 46.9±2.7%) and At (30.5±1.7 vs 49±3.2%) and significantly reduced the effect of AA (48.4±2.6 vs 59.5±3.1%). These data suggest activation of peripheral β-adrenoceptors in the delayed GE induced by phenylpyrazolone derivatives.